(untitled) (Journal of Current and Advance Medical Research, 2018)
Background: The wide spectrum of bone tumors, their rarity, diverse origin and tendency to produce overlapping anatomic patterns pose a definite diagnostic challenge to the orthopedic surgeons and the pathologists. Objective: The present study was intended to find the pattern of bone tumors and their anatomical locations, and histopathological characteristics in a tertiary care hospital of Dhaka. Methodology: A retrospective review of the histopathological records of patients with established diagnosis of bone tumors at National Institute of Traumatology and Orthopedic Rehabilitation (NITOR), Dhaka, Bangladesh was done from January 2015 to December 2016 for a period of two (02) years. The demographic data such as the age and sex, anatomical location and histopathological findings were studied from the existing records of the patients and their slides were reexamined. Bone lesions of inflammatory origin were excluded from this study leaving the lesions of both neoplastic and tumor-like origin for further study. Result: A total 283 cases of bone lesions were primarily included in the study. Bone lesions of inflammatory origin (n = 65) were excluded from this study leaving 218 lesions of both neoplastic and tumor-like origin for further study. The median age of the patients was 22 (range: 3 – 75) years. In terms of anatomical site of the tumors, over one-third (36.6%) was located in femur 21.1% in tibia, 12.2% in humerus, 6.1% in radius and 5.6% in ulna. In terms of types of bone tumor, 105(48.2%) were benign, 66(30.3%) malignant, 47(21.5%) tumor-like lesions. About 65% of the benign tumors were of Giant cell tumor, 28.5% were osteochondroma, 1% osteoma and 5.7% were of other types. Of the malignant tumors, one-third (33.3%) was of metastatic type, 27.3% Ewing’s sarcoma, 22.7% osteosarcoma, 9.1% chondrosarcoma and 4.6% were of other varieties. Conclusion: Primary bone tumors are mainly benign; however, giant cell and metastatic tumors are the most common benign and malignant bone tumors respectively. Journal of Current and Advance Medical Research 2018;5(1):23-28